EVIDENCE OF CYCLIC DUST DEPOSITION IN THE US GREAT PLAINS DURING THE LAST DEGLACIATION FROM THE HIGH-RESOLUTION ANALYSIS OF THE PEORIA LOESS IN THE EUSTIS SEQUENCE (NEBRASKA, USA) - Rousseau D.-D.; Rossignol J.; Antoine P.; Kunesch S.; Hatté C.; Gauthier C.; Packman S.; Lang A. (My University, 2007)
The Peoria Loess unit is a well-defined stratigraphical unit in the Upper Pleistocene of the North American Quaternary, deposited between 30-25 ka and about 12 ka ago. It has been indicated that this unit shows the highest known worldwide depositional rate for eolian deposits, as its thickness varies, near the source area, between 19 m and 46 m, extreme values that are not even recorded in the Chinese sequences. The results of our present investigation indicate that this particular unit is not homogenous. Its shows different subunits where lithological variation can be observed through the occurrence of embryonic gley horizons alternating with laminated loess. Furthermore the grain-size analysis shows cycles corresponding to variations in the eolian dynamics responsible for dust transportation and deposition. A grain size index interpreted as characterizing the eolian dynamics (higher values corresponding to stronger wind conditions) shows higher values than those observed in Europe. A comparison of this index is proposed with the Greenland dust and δ18O records. It shows that the main climatic history, as corresponding to events occurring mainly in North Atlantic domain, is recorded in the Peoria Loess deposits. However, the variation in the magnitude of the eolian events indicates differences from the European loess sequences. The strong North Atlantic coolings expressed by Heinrich events, as recorded in Europe by coarser deposits, are not differentiated in the studied sequence. Hence, they follow more closely observations obtained off California for the north-east Pacific domain. © 2007 Elsevier B.V. All rights reserved.
Keywords: EOLIAN DYNAMICS; EUSTIS; GRAIN SIZE; LAST DEGLACIATION; LOESS DEPOSITS; NEBRASKA; PEORIA LOESS; USA; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен